2020
DOI: 10.3390/nano10112288
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Thermal Conduction in Nanoparticle Aggregates in the Presence of Surfactants

Abstract: Many theoretical and experimental studies have shown that the addition of nanoparticles into conventional fluids may generate nanofluids with significantly improved heat transfer properties. In the present work, the effect of nanoparticle aggregation on the thermal conductivity of nanofluids is studied, considering also the effect of surfactants that are typically added to stabilise the nanofluid. A method for simulating aggregate formation is developed here that allows tailoring of the fractal dimension and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…In order to study the effect of polydispersity on thermal conductivity, the work developed in [ 38 ] has been extended to include polydispersed particles. This technique offered fast convergence of the algorithm for the representation of agglomerated systems with predetermined properties.…”
Section: Modelling Polydispersed and Sintered Aggregatesmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to study the effect of polydispersity on thermal conductivity, the work developed in [ 38 ] has been extended to include polydispersed particles. This technique offered fast convergence of the algorithm for the representation of agglomerated systems with predetermined properties.…”
Section: Modelling Polydispersed and Sintered Aggregatesmentioning
confidence: 99%
“…A new particle stochastically appears on the surface of the particle, and the process is repeated, with the restriction of no overlapping between any pair of particles. During the process, certain restrictions are imposed as described in [ 38 ], aiming at the convergence of the fractal dimension to the target value or range of values. It has been shown that the desired fractal dimension can be achieved with only a few particles.…”
Section: Modelling Polydispersed and Sintered Aggregatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Many published numerical and experimental studies on nanofluids fabricated with particles of carbon-based materials were found in the literature, which show the continued growth of interest in such materials [ 35 , 51 , 52 , 53 , 54 ]. Figure 4 classifies these documents in terms of the number of available publications at the Scopus database for each type of carbon-based material used in nanofluids production.…”
Section: Introductionmentioning
confidence: 99%